2022
DOI: 10.1002/alz.12789
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease as an innate autoimmune disease (AD2): A new molecular paradigm

Abstract: A new model of Alzheimer's disease (AD) is presented: Alzheimer's disease as an autoimmune disease (AD 2 ). In response to pathogen-/damage-associated molecular pattern-stimulating events (e.g., infection, trauma, ischemia, pollution), amyloid beta (Aβ) is released as an early responder cytokine triggering an innate immunity cascade in which Aβ exhibits immunomodulatory/antimicrobial duality. However, Aβ's antimicrobial properties result in a misdirected attack upon "self" neurons, arising from the electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…[ 69 ]. Recently, a new model of AD as an autoimmune disease of innate immunity has been theorized, in which Aβ would act as a cytokine-like immunopeptide, the target of an innate autoimmune response that fuels an auto-inflammatory process [ 70 ]. In this model, the modulation of endogenous anti-AD molecules would have a central therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ]. Recently, a new model of AD as an autoimmune disease of innate immunity has been theorized, in which Aβ would act as a cytokine-like immunopeptide, the target of an innate autoimmune response that fuels an auto-inflammatory process [ 70 ]. In this model, the modulation of endogenous anti-AD molecules would have a central therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, poor gut microbiota diversity in AD patients has gained an ongoing interest followed by finding an additional molecular pathogenesis for AD. Novel findings suggest that autoimmune and autoinflammatory mechanisms are engaged in AD 99 . The data suggested that SCFAs, such as butyric, propionic, acetic acids, and microbial metabolites in colon reduced the AD neuropathological features and other neurodegenerative diseases by providing alternative energy sources to the brain 100 .…”
Section: Neurodegenerative Diseases Treatment With Psychobioticsmentioning
confidence: 99%
“…The hallmark features of AD include the presence of extracellular amyloid-β plaques (Aβ), intracellular neurofibrillary tangles, and neurodegeneration. Of interest, AD is described as a brain-centric disorder of innate immunity involving simultaneous autoimmune and autoinflammatory mechanisms [ 70 ]. In response to initial (yet unknown) stimuli, Aβ is released as an early reactive immunopeptide, exhibiting both immunomodulatory and antimicrobial properties (in the presence or absence of bacteria), and triggering an innate immune cascade that causes a misdirected attack against “self” neurons.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%